An ex vivo cystic fibrosis model recapitulates key clinical aspects of chronic Staphylococcus aureus infection. Issue 1 (13th January 2021) - Sweeney, Esther; Harrington, Niamh E.; Harley Henriques, Alicia G.; Hassan, Marwa M.; Crealock-Ashurst, Branagh; Smyth, Alan R.; Hurley, Matthew N.; Tormo-Mas, María Ángeles; Harrison, Freya
Abstract : Staphylococcus aureus is the most prevalent organism isolated from the airways of people with cystic fibrosis (CF), predominantly early in life. Yet its role in the pathology of lung disease is poorly understood. In mice, and many experiments using cell lines, the bacterium invades cells or interstitium, and forms abscesses. This is at odds with the limited available clinical data: interstitial bacteria are rare in CF biopsies and abscesses are highly unusual. Bacteria instead appear to localize in mucus plugs in the lumens of bronchioles. We show that, in an established ex vivo model of CF infection comprising porcine bronchiolar tissue and synthetic mucus, S. aureus demonstrates clinically significant characteristics including colonization of the airway lumen, with preferential localization as multicellular aggregates in mucus, initiation of a small colony variant phenotype and increased antibiotic tolerance of tissue-associated aggregates. Tissue invasion and abscesses were not observed. Our results may inform ongoing debates relating to clinical responses to S. aureus in people with CF.